Effect of Situated Learning on Students’ Psycho-Productive Skills in Machine Woodworking in Technical Colleges in Rivers State - Holman Kodjo Akosubo (East Asian Journal of Multidisciplinary Research, 2023)
This research aims to examine the effect of situated learning on students’ psycho-productive skills in machine woodworking in technical colleges in Rivers State. Two research questions were posed to conduct the study, while two null hypotheses were formulated for the study. The population comprised all 160 National Technical Certificate (NTC) II woodwork students of two Government Technical Colleges. The instrument had a 0.76 Reliability Index using the KR-20 formula. The study found that situated learning is superior to the demonstration method in imparting psycho-productive skills in drilling operations in machine woodworking. The study also found that the group taught grinding operations with situated learning in machine woodworking performed better than the group taught grinding operations with the demonstration method. Based on the findings of the study, the following recommendations were made:  Situated learning should be adopted by curriculum developers and instructors as one of the participatory methods of machine woodworking teaching and learning in technical colleges in Rivers State.